Competition Council’s power to control economic activity - BARKAT , Imad eddinne (Journal of Human Sciences, 2025)
A specialized entity, known as the Competition Council, was established as an independent regulatory authority. The legislator has entrusted it with overseeing competition to protect the market from restrictive practices that might affect pricing and competition. The Council is responsible for addressing issues related to economic dominance or dependency, as well as prohibiting collusive agreements and economic alliances among businesses. Leveraging the powers granted by public authority, the Council enforces regulations to control, prevent, and penalize anti-competitive and price-related offenses. By doing so, it ensures that economic activities are conducted fairly and ethically.